The complete mitochondrial genome of the hybrid offspring Epinephelus fuscoguttatus ♀ × Epinephelus tukula ♂. Issue 2 (3rd July 2019) - Cheng, Meiling; Tian, Yongsheng; Li, Zhentong; Wang, Linna; Wu, Yuping; Zhang, Jingjing; Pang, Zunfang; Ma, Wenhui; Zhai, Jieming
Abstract: The hybrid offspring Epinephelus fuscoguttatus ♀ × E. tukula ♂ showed heterosis in terms of growth and disease resistance. The mitochondrial genome is 16, 629 bp in length and consists of 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes, and a control region. The difference of total length is mainly caused by the difference of length in non-coding region. The nucleotide base composition is A = 29.15%, G = 15.62%, T = 26.91%, C = 28.32%, A + T = 56.06%, and C + G = 43.94%. The phylogenetic analysis using neighbour-joining (NJ) method showed that the hybrid offspring has a closer relationship to E. fuscoguttatus × E. lanceolatus.